Management of Laparoscopic Surgery in Intraoperative Subcutaneous Emphysema: A Case Report - RTH Supraptomo (Indonesian Journal of Medicine, 2020)
Background: Over the past 50 years, laparoscopy has evolved from a limited gynecological surgical procedure that is only used for diagnosis and tubal ligation to become the main surgical tool used for many gynecological indications. Many studies have shown that laparoscopy is safer, more affordable, and has a shorter recovery time than laparotomy. This study aimed to report the management of laparoscopic surgery in intraoperative subcutaneous emphysema.Case Presentation: The subject of the study was a 37-year-old woman with adenomyosis and chocolate cyst of sinistra with a surgery plan for resection of adenomyosis and per laparoscopic cystectomy with the physical status of the ASA II Plan GAET. The surgery was carried out on October 15, 2018, with surgery for 5 hours. At the intraoperative, subcutaneous emphysema was found from the diaphragm to the thorax. In this condition, the peritoneal insufflation was reduced to 10-12 mmHg. The head down was returned to a position that made it easier for the patient's condition to reduce the occurrence of decreased lung compliance. The patient's postoperative condition was good, the hemodynamic was stable, her breath was spontaneous, and the saturation was 99% with oxygen supplementation via Nasal Kanul 3 lpm. The subcutaneous emphysema gradually disappeared 24 hours postoperatively. Conclusion: Subcutaneous emphysema may occur in the laparoscopic procedures. The close monitoring during surgery and the expertise of the anesthesiologist in diagnosing and intervening is crucial in controlling this condition.Keywords: subcutaneous emphysema; laparoscopy; intraoperative interventionCorrespondence: RTH. Supraptomo. Department of Anesthesiology and Intensive Therapy, Dr. Moewardi Hospital, Surakarta, Central JavaIndonesian Journal of Medicine (2020), 05(03): 206-213https://doi.org/10.26911/theijmed.2020.05.03.05